Striga newsletter - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
Striga newsletter, PASCON Technical Secretariat, FAO Regional Office for Africa, PO Box 1628, Accra, GHANA